1982
DOI: 10.1037/0735-7028.13.5.654
|View full text |Cite
|
Sign up to set email alerts
|

PhD and MA clinical psychologists and MSWs in public mental health settings: A nationwide comparison.

Abstract: A nationwide survey of public mental health facility directors solicited information and opinions comparing the employment opportunities, salaries, duties, and job skills of doctoral and subdoctoral clinical psychologists and MSWs. The results indicate that although all groups are in demand in the marketplace, receive competitive salaries, and are evaluated as competent service providers, subdoctoral clinicians consistently fall behind MSWs on all dimensions, and both, in turn, fall behind doctoral-level clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
10
0

Year Published

1985
1985
1999
1999

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 8 publications
1
10
0
Order By: Relevance
“…I recall that we suggested in the early 1980s that a terminal master's program be required to adhere to truth-in-advertising regulations and label their catalogs, "Warning: This degree may be hazardous to your employment opportunities." A nationwide study of comparative employment opportunities, salaries, duties, and job skills of those with master's degrees in social work (MSWs), doctoral clinical psychologists, and subdoctoral clinical psychologists indicated that the subdoctoral clinicians fell behind MSWs and both fell behind doctoral level clinical psychologists on all dimensions (Havens et al, 1982). In the eyes of the directors of mental health centers, they simply did not measure up.…”
Section: Remaining a Doctoral Professionmentioning
confidence: 99%
“…I recall that we suggested in the early 1980s that a terminal master's program be required to adhere to truth-in-advertising regulations and label their catalogs, "Warning: This degree may be hazardous to your employment opportunities." A nationwide study of comparative employment opportunities, salaries, duties, and job skills of those with master's degrees in social work (MSWs), doctoral clinical psychologists, and subdoctoral clinical psychologists indicated that the subdoctoral clinicians fell behind MSWs and both fell behind doctoral level clinical psychologists on all dimensions (Havens et al, 1982). In the eyes of the directors of mental health centers, they simply did not measure up.…”
Section: Remaining a Doctoral Professionmentioning
confidence: 99%
“…Both national and regional data indicate that MAlevel personnel are the main providers of psychological services in the public sector, from the state hospitals to the community mental health system (Dimond, Havens, Rathnow, & Colliver, 1977;Havens, Colliver, Dimond, & Wesley, 1982;Stevens, Yock, & Perlman, 1979;Perlman, 1985). In fact, the rapid growth of applied MA programs during the 1960s and 1970s, primarily at regional state universities, paralleled the growth of the community mental health movement.…”
Section: Responding To Personnel Needs In the Public Sectormentioning
confidence: 99%
“…The previously mentioned survey by Havens et al (1982) shed a new light on the situation, however. Although it was found that subdoctoral clinical psychologists were in demand in the marketplace, received positive ratings on professional competence and academic background, and were viewed by their employers as providing a positive contribution to the operation of their agencies, this group tended to fall behind both MSWs and doctoral-level practitioners on almost all dimensions of consideration.…”
mentioning
confidence: 99%